Analisis Strategi Segmntation, Targeting, dan Positioning dalam Mengingkatkan Volume Penjualan pada Kedai Kopi Roemah Aki’q Surabaya - Daru Teja Sasangka; Acep Samsudin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research employs a qualitative descriptive method with the aim of understanding the segmentation, targeting, and positioning strategies to enhance sales volume at